P130Cas, Crk‐Associated Substrate, Plays Important Roles in Osteoclastic Bone Resorption. (December 2013) - Nagai, Yoshie; Osawa, Kenji; Fukushima, Hidefumi; Tamura, Yukihiko; Aoki, Kazuhiro; Ohya, Keiichi; Yasuda, Hisataka; Hikiji, Hisako; Takahashi, Mariko; Seta, Yuji; Seo, Sachiko; Kurokawa, Mineo; et al.
ABSTRACT p130Cas, Crk‐associated substrate (Cas), is an adaptor/scaffold protein that plays a central role in actin cytoskeletal reorganization. We previously reported that p130Cas is not tyrosine‐phosphorylated in osteoclasts derived from Src‐deficient mice, which are congenitally osteopetrotic, suggesting that p130Cas serves as a downstream molecule of c‐Src and is involved in osteoclastic bone resorption. However, the physiological role of p130Cas in osteoclasts has not yet been confirmed because the p130Cas‐deficient mice displayed embryonic lethality. Osteoclast‐specific p130Cas conditional knockout (p130CasΔOCL–) mice exhibit a high bone mass phenotype caused by defect in multinucleation and cytoskeleton organization causing bone resorption deficiency. Bone marrow cells from p130CasΔOCL– mice were able to differentiate into osteoclasts and wild‐type cells in vitro. However, osteoclasts from p130CasΔOCL– mice failed to form actin rings and resorb pits on dentine slices. Although the initial events of osteoclast attachment, such as β3‐integrin or Src phosphorylation, were intact, the Rac1 activity that organizes the actin cytoskeleton was reduced, and its distribution was disrupted in p130CasΔOCL– osteoclasts. Dedicator of cytokinesis 5 (Dock5), a Rho family guanine nucleotide exchanger, failed to associate with Src or Pyk2 in osteoclasts in the absence of p130Cas. These results strongly indicate that p130Cas plays pivotal roles in osteoclastic bone resorption. © 2013 American Society for Bone and Mineral Research.